The role of the new Evenkiness in the Evenki language revitalization: the case of the Sakha Republic (Yakutia) - Sivtseva, Mira (UiT Norges arktiske universitet, 2015)
This thesis is devoted to the awakened indigenous identity of the Evenki people and its role in the Evenki language revitalization in the Sakha Republic (Yakutia), Russia. My personal experience of being an indigenous person in a multiethnic and multilingual society has become the main driving force for writing this thesis. I have personally experienced a rediscovery of my ethnic identity during the research process. Most indigenous languages in Russia are endangered; the Evenki language is not an exception. This study examines the reasons for the Evenki language shift and loss, the development of the Evenki ethnic identity in the USSR and Russia, and the role of the new Evenkiness in the Evenki language revival. Through ten semi-structured and unstructured interviews with representatives of three Evenki generations, the study examines their experiences of being Evenki in the multicultural state. The main finding of this thesis is the interconnection between what I call a new Evenki ethnic identity (new Evenkiness) and the willingness of the Evenki people to revitalize their mother tongue. Thus, the Evenki who feel the awakening of their indigenous ethnic identity feel the responsibility for their native language and its vitality. Among the factors which have informed the emergence of the new Evenkiness are interconnectedness and exchange of experiences with other indigenous peoples, participation in indigenous forums, conferences, and, last but not least, the formation of the new state of the Russian Federation.